Epithets of Cities and Regencies in East Java - A. Syihabuddin Aniq Jimly (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This paper aims to discuss the epithets of cities and regencies in East Java, starting from the use of language in epithets, the structure of epithets, the classification of epithets, to how East Javanese people view epithets. This research was written using a qualitative approach. The results show that there are three languages used in epithets, namely Indonesian, English, and Javanese. Then, the words in the epithet are nouns and the syntactic structure in the epithet is a noun phrase that has the structure pattern [Noun + Noun] and [Determiner + Noun + Prepositional Phrase]. The epithet data is classified into 9 (nine) categories, namely culinary, natural resources, industry, history, motto, geographical conditions, social and cultural, slogan, and education. Javanese people think that the epithets of cities and regencies are used as an identity of pride, regional promotion, and boosting the regional economy. In addition, ecologically, the epithets can awaken society enthusiasm in conserving the environment.